Hubungan Kemandirian Belajar Daring dengan Hasil Belajar IPS Siswa Kelas V SD Gugus V - Rina Reskiana; Makmur Nurdin; Rosmalah Rosmalah (STKIP Andi Matappa Pangkep, 2021)
The study is a correlational study that aims to determine whether or not there is a relationship between online learning independence and social studies learning outcomes for Vth grade students of SD Cluster V East Tanete Riattang District Bone Regency. The population in this study were all V grade students of SD Cluster V East Tanete Riattang District, Bone Regency, while the number of samples in this study was 74 students. Data collection is done by providing questionnaires and documentation. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. Based on descriptive statistical analysis data obtained online learning independence with an average of 110,42 and a percentage of 69,17% in the good category, and students social studies learning outcomes with an average of 78,53 and a percentage of 78,88% in the good category. The results of inferential statistical analysis obtained tcount ≥ ttable at the 5% significance level. Thus H0 is rejected and H1 is accepted. The conclusion in this study is that there is a significant relationship between learning independence and social studies learning outcomes for Vth grade students of SD Cluster V East Tanete Riattang District Bone Regency.